Effect of angiotensin-converting enzyme inhibitor Hoe-498 on noradrenaline-induced vasoconstriction in isolated perfused mesentery of rats - XIANG Ji-zhou; Schölkens B A (Acta Pharmacologica Sinica, 2016)
Oral administration of Hoe-498(1 mg/kg) to rats attenuated the vasoconstriction of perfused mesenteric vessels induced by NE. It is suggested that Hoe-498 interferes in the angiotensin-mediated facilitation of adrenergic neurotransmission.